PERSEPSI MAHASISWA SASTRA INDONESIA TERHADAP PENGGUNAAN GOOGLE TRANSLATE (INDONESIA-INGGRIS) SEBAGAI WADAH PENERJEMAHAN TEKS - Mardiana, Mardiana; Anshari, Anshari; Mahmudah, Mahmudah (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2022)
This study aims to examine the use of Google Translate in translating Indonesian abstract texts into English abstract texts by using the perceptions of students of the  Indonesian Language and Literature Study Program in order to determine whether or not the translation results from Google Translate contained in Google Translate are accurate or inaccurate. using Newmark's theory of semantic translation. This type of research is qualitative with a descriptive attitude. The data used is the student's perception of the use of Google Translate. The data sources used in this study were students of the Indonesian Language and Literature Study Program.